Genotypic differences in root architecture and physiological characteristics in mango (Mangifera indica) under drought - SANDEEP; DUBEY, A K; SHARMA, NIMISHA; AWASTHI, O P; SHARMA, R M; DAHUJA, ANIL (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi during 2020 and 2021 to study the genotypic differences in root architecture and physiological characteristics in mango (Mangifera indica L.) under drought. One-year-old polyembryonic 7 mango rootstock genotypes were exposed to normal irrigation and drought conditions for 24 days. The drought-induced increased total plant weight and dry weight in Kurukkan. The shoot dry weight decreased in all genotypes ranging from 5.13% in OLP-Z-6/1 to 81.82% in Kurukkan. There was a lesser reduction in membrane stability index in Kurukkan and K-5, stomata count in Kurukkan, Olour and OPK-3-7/12 at the end of the drought period. Root surface area increased under drought in Kurukkan, while it decreased more in K-5. Correlation studies confirmed a strong positive relationship between relative water content (RWC) and membrane stability index (MSI), number of stomata (SC), number of leaves (NL), root tips (RT) and root forks (NRF); MSI and number of root tips (NRT); dry weight of the whole plant and root surface area (RSA); the dry weight of roots and root volume (RV), RSA, and plant height (Ph); root length (RL) and RSA, RT, and NRF. Kurukkan was identified as drought-tolerant based on a higher SC, RWC, RV, RSA, dry mass, NRT and NRF. Results indicated that the root indices offer a promising strategy for the screening of drought-tolerant mango genotypes.